Answered

Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Solve each system by substitution
Y=6x-11
-2x-3y=-7


Sagot :

you just plug in what Y equals into the second equation:
-2x-3(6x-11) = -7
then you solve the equation:
-2x-18x+33 = -7
-20x+33 = -7
subtract 33 from each side:
-20x = -40
divide each side by -20
x = 2
then you plug x into the original equation:
y = 6(2)-11
y = 12-11
y = 1
so x = 2 and y = 1
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.